Thrombotic events in patients with antiphospholipid syndrome and their prophylactic management. - Moreno-Gomez , Freddy (2022)
The antiphospholipid syndrome (APS) is a clinical condition whose main form of presentation is thrombosis of various vascular beds, leading to multiple complications that represent a threat to the life of patients. Therefore, the goal of this review is to present the current recommendations on the management of the syndrome, in addition to emphasizing the existence of therapeutic alternatives other than vitamin K inhibitors. The exploration of multiple international guidelines regarding the management of APS allowed to establish that Warfarin continues to be the pillar of management for the thrombotic manifestations of the disease, and DOACs aren´t recommended for patients with APS due to recurrent thrombosis associated to this product. More clinical trials and research are required to safely recommend the use of therapies other than Warfarin in APS.